Exploring the care experiences of hemodialysis nurses: from the cultural sensitivity approach - Hsu Jui-Chin; Chung Fen-Fang; Lee Tso-Ying; Wang Pao-Yu; Lin Mei-Hsiang (BMC, 2024)
Abstract Background Culturally sensitive care has been identified as a best-practice approach for improving health outcomes. Hemodialysis patients require culturally sensitive care because it involves totally changing their previous life. The purpose of this study was to explore the subjective experiences of hemodialysis nurses in providing culturally sensitive care to hemodialysis patients. Methods A qualitative study was carried out in the hemodialysis center of a teaching hospital in northern Taiwan. Purposive sampling and semi-structured interview guidelines were employed to interview 23 hemodialysis nurses. The interviews were recorded and transcribed verbatim, and the resulting data were analyzed and summarized using content analysis by constant comparative methods. Results Hemodialysis nurses exhibited the characteristics for delivering culturally sensitive care, which comprised five aspects: finding the true meaning of the behavior of the participants, recognizing and honoring individual psychological states, culturally sensitive communication in line with patients' values, customizing care content through cultural transformation strategies, and empowerment rather than prohibition. Conclusions The findings of this study on the culturally sensitive care provided by hemodialysis nurses can be utilized by nursing educators and administrators as a reference to develop and enhance the nursing education related to culturally sensitive care for hemodialysis professionals.